Metagenomic next-generation sequencing (mNGS) versus tissue culture technique (TCT) in diagnosis of spinal infection: a systematic review and meta-analysis - Yan-Cheng Li; Yan-Xiao Liu; Lei Li; Hua Wang; Zi-Ru Zhao; Zhi-Yuan Yao (Scientific Reports, 2025)
Abstract Spinal infections pose a significant clinical challenge due to the difficulty of early diagnosis. Traditional Tissue Culture Technique (TCT) has limitations, while Metagenomic Next-Generation Sequencing (mNGS) has emerged as a promising diagnostic tool. However, reports on the diagnostic performance of mNGS and TCT for spinal infections are inconsistent, and there has been a lack of systematic analysis of the evidence. This systematic review and meta-analysis included 10 studies involving a total of 770 patients to compare the diagnostic accuracy of mNGS and TCT. A comprehensive literature search was conducted using PubMed, Embase, Web of Science, Cochrane Library, and SinoMed to identify studies evaluating the diagnostic accuracy of mNGS and TCT for spinal infections. Data were analyzed using Review Manager 5.3 and Stata 16.0 to compute the sensitivity, specificity, and Area Under the Summary Receiver Operating Characteristic Curve (AUC). The meta-analysis revealed pooled estimates for mNGS with a sensitivity of 0.81 (95% CI, 0.74–0.87), specificity of 0.75 (95% CI, 0.48–0.91), and an AUC of 0.85 (95% CI, 0.82–0.88). In contrast, pooled estimates for TCT showed a sensitivity of 0.34 (95% CI, 0.27–0.43), specificity of 0.93 (95% CI, 0.79–0.98), and an AUC of 0.59 (95% CI, 0.55–0.63). While mNGS demonstrates higher sensitivity and overall diagnostic accuracy than TCT, its lower specificity suggests that it may be most effective when used alongside conventional methods to enhance diagnostic reliability in spinal infections.